MENINGKATKAN KESADARAN KESELAMATAN BERLALU LINTAS MELALUI PROGRAM PEMBINAAN DAN SOSIALISASI DI SMK KOLESE TIARA BANGSA: Improving Traffic Safety Awareness through Mentoring and Socialization Programs at SMK Kolese Tiara Bangsa - Tukino Tukino; Syahril Effendi; Nanda Harry Mardika; Algifanri Maulana; Arif Rahman Hakim (PUAN INDONESIA, 2023)
Technological advancements have greatly impacted the transportation system on highways, including the diverse modes of transportation used by people today. Possessing a mode of transportation has become a status symbol among both the young and elderly members of the community. However, research shows that traffic accidents claim 1.3 million lives each year, with over 3,000 fatalities occurring daily. Batam, an Indonesian city, has the highest rate of traffic accidents, with statistics projecting a 47% increase in accidents from 2021 to 2022. At SMK Kolese Tiara Bangsa, over 80% of students commute to school on motorcycles, emphasizing the need to encourage the socialization of Traffic Safety program in driving ethics for students both inside and outside of school to raise awareness of driving ethics and traffic safety, maintain security, order, and safety on the road.